Variations in RTI Literacy Implementation in Grades 6-12: A National Study. Issue 1 (2nd January 2022) - Savitz, Rachelle S.; Allen, Abigail A.; Brown, Christy
ABSTRACT: Despite the need for Response to Intervention (RTI) in secondary grades, research is scant with most studies exploring state-level policy guidance and RTI implementation surveys in classrooms. Additionally, state and federal policy has generally been vague regarding specific information for RTI implementation in literacy. Our national survey reports data on RTI implementation from 209 secondary grade teachers. Response profiles and statistical significance tests were conducted, determining that many secondary level classrooms are using research-based recommendations for RTI implementation and practice across the country. However, significant regional differences exist in how RTI is being resourced and implemented.